2015
DOI: 10.1001/jama.2015.8881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Testosterone Administration for 3 Years on Subclinical Atherosclerosis Progression in Older Men With Low or Low-Normal Testosterone Levels

Abstract: IMPORTANCE Testosterone use in older men is increasing, but its long-term effects on progression of atherosclerosis are unknown.OBJECTIVE To determine the effect of testosterone administration on subclinical atherosclerosis progression in older men with low or low-normal testosterone levels. DESIGN, SETTING, AND PARTICIPANTS Testosterone's Effects on Atherosclerosis Progression inAging Men (TEAAM) was a placebo-controlled, double-blind, parallel-group randomized trial involving 308 men 60 years or older with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(125 citation statements)
references
References 49 publications
4
116
1
4
Order By: Relevance
“…Results from a recently published placebo-controlled, randomized trial on testosterone treatment including older, community-dwelling men with testosterone levels in the lower range indicated that there are no beneficial effects of testosterone administration in healthy men on the risk of atherosclerosis in line with our interpretation of the current study (28).…”
Section: Cardiovascular Diseasesupporting
confidence: 84%
“…Results from a recently published placebo-controlled, randomized trial on testosterone treatment including older, community-dwelling men with testosterone levels in the lower range indicated that there are no beneficial effects of testosterone administration in healthy men on the risk of atherosclerosis in line with our interpretation of the current study (28).…”
Section: Cardiovascular Diseasesupporting
confidence: 84%
“…The lack of definite response in some areas does not diminish the clearly proven efficacy in others, including areas of considerable importance to men. Some studies have reported no sexual benefits with T therapy, such as the study by Basaria et al 84 Notably, however, their study population was recruited without a requirement for baseline symptoms and included men with normal T concentrations. There is no reason to expect men without symptoms to have symptomatic improvement with treatment, particularly if they do not have true TD.…”
Section: Discussionmentioning
confidence: 97%
“…Out of 284 retrieved articles, 14 were included in the study [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. However, one study [24] not adequately reporting p values or mean differences was used only when standardized effect size calculations (standardized difference in means [SDM]) were performed.…”
Section: Studies Characteristicsmentioning
confidence: 99%